STRATEGI PENINGKATAN KINERJA END USER MELALUI PENGGUNAAN APLIKASI TNDE PT. ANGKASA PURA I (PERSERO) - Wahyudianto, Dariska; D, Derriawan; T, Tabroni (SEKOLAH PASCASARJANA PRESS, 2020)
The purpose of this study was to determine the effect of ease of learning and the quality of information technology through ease of use and end user trust in applications on the performance of end users with end user satisfaction as a moderator variable. The population of this research is the employees of PT. Angkasa Pura I (Persero). The number of samples from the population were 245 people taken using nonprobability sampling techniques. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the LISREL program. This research results in the ease of learning variables and the quality of information technology through ease of use and end user trust in applications have a positive and significant effect on end user performance, and the role of end user satisfaction in moderating end user performance, while the ease of learning variable directly influences no significant effect on end user trust in the application.